Vertical arrays of SiNWs-ZnO nanostructures as high performance electron field emitters - Devarapalli, Rami Reddy; Shinde, Deodatta R.; Barka-Bouaifel, Fatiha; Yenchalwar, Sandeep G.; Boukherroub, Rabah; More, Mahendra A.; Shalke, Manjusha V. (Journal of Materials Chemistry, 2012)
Multicomponent hybrid materials of nanostructured building blocks are essential for the development of complex devices and advanced applications due to their role as either functional or interconnecting elements. This study introduces a simple and cost effective strategy for the synthesis of vertical arrays of silicon nanowires and ZnO nanostructures (nanorod and multipod structures). Formation of vertical nanostructured arrays is confirmed by SEM and HRTEM imaging as well as XRD and Raman measurements. We have investigated field emission properties of the as-synthesized vertical nanostructured arrays. Our results show that these SiNWs-ZnO nanostructures are highly efficient and stable field emitters.

Vapor-liquid-solid growth of one-dimensional tin sulfide (sns) nanostructures with promising field emission behavior - Suryawanshi, Sachin R.; Warule, Sambhaji S.; Patil, Sandip S.; Patil, Kashinath R.; More, Mahendra A. (ACS Applied Materials & Interfaces, 2014)
Single-crystalline ultralong tin sulfide (SnS) nanowires has been grown by a thermal evaporation technique under optimized conditions on gold-coated silicon substrates, and for the first time, field emission investigations on the SnS nanowires at the base pressure of 1 X 10(-8) mbar are reported. It has been revealed that the surface morphology of the as-synthesized SnS nanostructures is significantly influenced by the deposition temperature and duration. Structural and morphological analyses of as-synthesized SnS nanostructures have been carried out using X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). To understand the optical and electronic properties of as-synthesized SnS nanowires, ultraviolet-visible (UV-vis), photo-luminescence (PL), and X-ray photoelectron spectroscopy (XPS) studies were carried out. The SEM and TEM measurements reveal the formation of ultralong SnS nanowires, with an average diameter of 80 nm. A plausible explanation on the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, the field emission characteristics of the SnS nanowires are found to be superior to the other metal chalcogenide nanostructures. The synthesized SnS nanowire emitter delivers a high current density of similar to 2.5 mA/cm(2) at an applied electric field of similar to 4.55 V/mu m. The emission current stability over a period of 6 h is observed to be good. The observed results demonstrate the potential of the SnS nanowire emitter as an electron source for practical applications in vacuum nano/microelectronic devices.
Keywords: Electron emission; ID nanostructure; SnS nanowires; thermal evaporation; vapor-liquid-solid (VLS) growth

Vapour-liquid-solid growth of one-dimensional In2Se3 nanostructures and their promising field emission behaviour - Suryawanshi, Sachin R.; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J. (RSC Advances, 2015)
Single crystalline ultra long In2Se3 nanowires have been grown by employing a single step facile thermal evaporation route under optimized conditions on Au/Si wafers, and morphology dependent field emission investigations on the In2Se3 nanostructure at the base pressure -1 x 10(-8) mbar are explored. In addition, structural and morphological analysis of as-synthesized In2Se3 nanostructures has been carried out using XRD, SEM and TEM. A plausible explanation of the vapor-solid-liquid (VLS) growth mechanism based on the experimental results and reported literature has been presented. Furthermore, field emission measurements demonstrate remarkably enhanced emission behaviour, which is explained on the basis of the field enhancement factor and aspect ratio of the nanostructures. The synthesized In25e3 nanowire emitter delivers a very high current density of -1.2 mA cm(-2) at an applied electric field of -6.33 cm(-1). The present results demonstrate In2Se3 as an important candidate for potential applications in nano/micro-electronic devices.